Perencanaa Buku Katalog Fotografi Sebagai Media Informasi Dan Promosi Di Kampung Sampireun Resort & Spa - Najib, Moh Farid; Prameswari, Herdina (Akademi Sekretari Manajemen Taruna Bakti, 2023)
Intention in visiting tourist attractions can be increased by doing promotions. In addition to promotion, through the information media used, it must be able to meet customer needs. One of the effective information media that can be used is a catalog. The purpose of this paper is to find out the manufacture of a photography catalog book that contains information and photos of the products or services offered. The method used by the author in making this catalog book project is the glass box method, which starts from problem identification, concept development, design, testing and printing, editing, material searching, improvement and distribution. In addition, qualitative methods through in-depth interviews were conducted. The results of the design resulted in a printed version of the photography catalog book and a digital version. The feedback of the printed version of the photography catalog book shows that the catalog book facilitates the dissemination of information, the design is good, complete and able to explain the information needed, while the feedback on the digital version shows that the number of people who clicked on the catalog fluctuated.